FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERLANJUTAN PETANI BERUSAHATANI PADI SAWAH (Studi Kasus di Desa Pulau Aro Kecamatan Tabir Ulu Kabupaten Merangin) - Rosyani; Tri Kurnia, Lisa; Farida, Aulia (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2021)
This research aimed ; 1) to know the factors affecting the farmers in farming rice field in the village of Pulau Aro, Merangin District, 2) to know the status of sustainability of farming rice field in the village of Pulau Aro, Merangin District, 3) to analyze the influence between factors and sustainability of farming rice field in the village of Pulau Aro, Merangin District. Data collecting method wastaken from primary and secondary data. Determining the location was chosen purposely (purposive sample) by considering that Pulau Aro had unique traditions or habits in farming rice field while the respondents were done by simple random sampling with 67 respondents who joined into farmer group. The data were processed and analyzed by using multiple linear regression analysis to know the status of sustainability of farmingrice field, and then described to know the sustainability status of farming rice field. Result of multiple linear regression analysis that described the sustainability status of farming rice filed was that overall ecological aspects, social aspects and economic aspects were in a less sustainable category with R-Squared value of 53.24%. If viewed from each aspect, the social aspect was in a fairly sustainable category because the trainers were active in giving information and the farmers also participated in farmer group sactivities. While ecological aspects were less sustainable because farmers tended to use chemical drugs in fertilization and eradication of pests and rice diseases, while from the economic aspect of rice field was in the category of less sustainable because the production of farmers in rice field had not fulfilled the needs of farmers.